A Comparative Study of Certain Selected Industries Under Subsector Economics - Planning Commission (Planning Commission, 1980)
At the instance of the Planning Commission, New Delhi, the Consulting and Applied Research Division of the Administrative Staff College of India undertook the project entitled "A Comparative Study of Certain Selected Industries under Sub-Sector Economics". The study mainly aims at highlighting the sub-sectoral economics within each selected industry and finding out the relative efficiency of different sectors with reference to certain indices like the economic coefficients arrived at on the basis of the information collected for the representative units regarding capital, employed, costs of production, persons employed, value of output, value of input, depreciation, value added etc.
Consulting and Applied Research Division Administrative Staff College of India
Government of India, Planning Commission